A Deixis Analysis In The Song Lyrics Of Night Changes By One Direction - Nurul Fauziyah; Desy Rusmawaty; Susilo; Dyah Sunggingwati; Ventje Kalukar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the types and pragmatic functions of deixis in One Direction’s song “Night Changes.”Using a qualitative analysis content method, the research applies Levinson’s (1983) typology of person, time, place, discourse, and social deixis. The data were collected from the official lyrics and analyzed using Miles and Huberman’s (1994) model of data reduction, display, and conclusion drawing. A total of 39 deictic expressions were identified, consisting of person deixis (22 instances), time deixis (8), place deixis (4), discourse deixis (3), and social deixis (2). The findings show that person deixis is the most frequent, highlighting the narrative perspective and interpersonal involvement between the singer and the listener, while social deixis is the least frequent, reflecting the informal tone of the lyrics. This study demonstrates how deixis constructs narrative flow and emotional engagement in pop lyrics, with practical use in EFL classrooms and translation studies.